Implementation of active-reflective method to analyze students’ creative, communication and self-confidence abilities in mathematics learning - I N Atikah; E C M Asih (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Creative ability is important for facing competition in a world that more advanced because creativity is capital to face the challenges. In addition it required communication skills to convey the creativity that will give rise to confidence with capabilities. This research aims to know the ability of creativity, communication and self confidence of the students use active-reflective learning methods. This active-reflective learning methods belonged in a good criteria. The instruments used are the creative ability test, a test of the ability of communication and the sheets of measure students affective. The results showed that students have a creative and communication capability good enough with the ability to self confidence which is also good.